PERSPECTIVE ON BARRIERS TO E-LEARNING: INSIGHT FROM INDONESIAN PARENTS - Ginting, Pirman; Fahmi, Muhammad Khoirul; Saragih, Mandra; Piliang, Muliana; Hasnah, Yenni (TELL - US JOURNAL, 2023)
The phenomenon of online learning has grown at a rapid pace over the years. Despite its benefits, online learning also comes with certain drawbacks, such as a shortage of access to reliable network connectivity, digital literacy, and socializing. The current study aims to explore the perceptions of parents regarding the challenges of distance learning faced by their children in Indonesia. Questionnaires via google forms and interviews were used to diagnose the parents’ responses to handicaps that existed during distance learning. The participants comprised 30 parents whose children joined online schooling. The findings revealed that parents experienced various kinds of obstacles in their efforts to help their children learn remotely such as (1) personal barriers (2) technical barriers (3) logistical barriers, and (4) financial barriers. The trend toward online learning is projected to continue and grow in the coming years with more dialogical, synchronic, pluralist, open, and accessible to various groups.